Studying emigration by extending a large-scale household survey. Methodology, evaluation and descriptive findings - Zsuzsa Blasko\' (Hungarian Demographic Research Institute, 2015)
The present paper introduces the methodology of a pilot study on emigrants carried out in the framework of the SEEMIG project~ in Hungary and Serbia during 2013. Besides presenting the study design, key methodological lessons are drawn and an evaluation of the design is provided based on research results from Hungary. From these we conclude that the study was successful in providing valuable methodological insights that will no doubt lead to future improvements in collecting information about emigration. Furthermore, it has also yielded a rich set of indirectly collected data on an exceptionally large sample of emigrants, even though the data needs to be dealt with and considered with care. Making the first step in utilising this data, the paper also provides a descriptive analysis of the composition of the emigrant population from Hungary. Along with other results, the analysis shows that mostly young people, predominantly those in their twenties and thirties are leaving the country and that higher education graduates are significantly overrepresented among them.
Keywords: N33; 300; brain drain; labour migration; migrant; migration; out migration; survey; methodology; Labour Force Survey; Hungary; Internationale Migration; Auswanderung; Arbeitsmigranten; Erhebungstechnik; Ungarn